Oxidative insertion of amines into conjugated macrocycles: transformation of antiaromatic norcorrole into aromatic azacorrole. Issue 25 (10th March 2023) - Li, Sha; Sun, Yahan; Li, Xiaofang; Smaga, Oskar; Koniarz, Sebastian; Pawlicki, Miłosz; Chmielewski, Piotr J.
Abstract : A new group of aromatic porphyrinoids was obtained by an oxidative insertion of primary amines into the antiaromatic ring of 5, 14-dimesityl-norcorrolatonickel(ii ) activated by iodosobenzene. Abstract : A new group of aromatic porphyrinoids was obtained by an oxidative insertion of primary amines into the antiaromatic ring of 5, 14-dimesityl-norcorrolatonickel(ii ) activated by iodosobenzene. The substituted 10-azacorroles thus formed were characterized by spectroscopic and electrochemical methods, and XRD analysis. Protonated forms of azacorroles were shown to remain aromatic despite disconnection of the original π-electron delocalization path.